Targeting gastrointestinal nutrient sensing mechanisms to treat obesity. (December 2017) - Norton, Mariana; Murphy, Kevin G
Highlights: Gastrointestinal nutrient sensors detect macronutrient break-down products. Nutrient sensing by enteroendocrine cells alters appetite-regulating hormone release. These nutrient sensing systems are potential targets for anti-obesity therapies. Abstract : Gut hormones have important roles in the regulation of appetite and glucose homeostasis. Understanding how macronutrient sensing in the gastrointestinal tract modulates gut hormone release may reveal novel pharmacological or dietary approaches to metabolic disease. In this short review we discuss the mechanisms by which the gut senses macronutrients and the products of macronutrient digestion, and their putative utility in treating obesity and related conditions.